Coherent Raman Imaging of Live Muscle Sarcomeres Assisted by SFG Microscopy - Hyunmin Kim (Nature Portfolio, 2017)
Abstract In this study, we used spectrally focused coherent anti-Stokes Raman scattering (spCARS) microscopy assisted by sum-frequency generation (SFG) to monitor the variations in the structural morphology and molecular vibrations of a live muscle of Caenorhabditis elegans. The subunits of the muscle sarcomeres, such as the M-line, myosin, dense body, and α-actinin, were alternatively observed using spCARS microscopy for different sample orientations, with the guidance of a myosin positional marker captured by SFG microscopy. Interestingly enough, the beam polarization dependence of the spCARS contrasts for two parallel subunits (dense body and myosin) showed a ~90° phase difference. The chemically sensitive spCARS spectra induced by the time-varying overlap of two pulses allowed (after a robust subtraction of the non-resonant background using a modified Kramers–Krönig transformation method) high-fidelity detection of various genetically modified muscle sarcomeres tuned to the C-H vibration (2800–3100 cm−1). Conversely, SFG image mapping assisted by phase-retrieved spCARS spectra also facilitated label-free monitoring of the changes in the muscle content of C. elegans that are associated with aging, based on the hypothesis that the C-H vibrational modes could serve as qualitative chemical markers sensitive to the amount and/or structural modulation of the muscle.